3D Printing of Hydrogels for Stretchable Ionotronic Devices. (21st September 2021) - Ge, Gang; Wang, Qian; Zhang, Yi‐Zhou; Alshareef, Husam N.; Dong, Xiaochen
Abstract: In the booming development of flexible electronics represented by electronic skins, soft robots, and human–machine interfaces, 3D printing of hydrogels, an approach used by the biofabrication community, is drawing attention from researchers working on hydrogel‐based stretchable ionotronic devices. Such devices can greatly benefit from the excellent patterning capability of 3D printing in three dimensions, as well as the free design complexity and easy upscale potential. Compared to the advanced stage of 3D bioprinting, 3D printing of hydrogel ionotronic devices is in its infancy due to the difficulty in balancing printability, ionic conductivity, shape fidelity, stretchability, and other functionalities. In this review, a guideline is provided on how to utilize the power of 3D printing in building high‐performance hydrogel‐based stretchable ionotronic devices mainly from a materials' point of view, highlighting the systematic approach to balancing the printability, printing quality, and performance of printed devices. Various 3D printing methods for hydrogels are introduced, and then the ink design principles, balancing printing quality, printed functions, such as elastic conductivity, self‐healing ability, and device (e.g., flexible sensors, shape‐morphing actuators, soft robots, electroluminescent devices, and electrochemical biosensors) performances are discussed. In conclusion, perspectives on the future directions of this exciting field are presented. Abstract : Hydrogel ionotronics prepared via 3D printing have received intensive attention due to the combination of high biocompatibility, stimuli‐responsiveness, rapid prototyping, and delicated patterns. Herein, recent advances in 3D printed hydrogel devices are reviewed, highlighting strategies to enhance printing quality (printability, resolution, and shape fidelity), properties (elastic conductivity, and self‐healing ability), and performances of various ionotronic devices.